A COMPARATIVE STUDY OF THREE BRANDS OF BIOSYNTHETIC HUMAN INSULIN: Biosynthetic Human Insulin - Zakaria, Manzar; Hameed, Shahid (Pakistan Armed Forces Medical Journal, 2008)
Objective: To compare the activity of three brands of regular biosynthetic human insulin (BHI) in healthy normal subjects with the glucose clamp technique.  Design: A comparative study.  Place and Duration of Study: CMH Lahore from May 2007 to July 2007. Patients and Methods: Thirty healthy normal male volunteers who met the inclusion criteria were tested.  Each insulin preparation was sequentially infused through intravenous route at 0.02 U/kg/h for 2 hour, 0.032 U/kg/h for 2 hour and finally at 0.05 U/kg/h for 2 hours.  A simultaneous 25% glucose infusion was maintained and the amount the glucose consumed was calculated. All subjects were studied on three different occasions with the three brands of insulin.  Blood glucose was monitored at regular intervals and its level was kept constant (clamped) at a baseline.  The amount of glucose infused was calculated for each insulin dose for the three brands of BHI.  Results: Mean values of glucose administered during the six hour infusion period for the three brands ranged between 162 to 190 g. The mean glucose consumed with 0.02 units/kg/hr of Zansulin, Actrapid and Humulin were 26.7gm, 30.6gm and 31.2gm respectively. Similarly the mean glucose consumed with 0.032 units/kg/hr of Zansulin, Actrapid and Humulin were 53gm, 59.7gm and 62.1gm respectively and a similar pattern of glucose consumption was observed for insulin dose of 0.05 units/kg/hr. Glucose administered during the 6 hour infusion differed significantly among the three brands of insulin, (p